Neuroticism: The Elephant in the Room - Santos, T (2014)
The term neurosis has a long tradition in psychiatric nosology. It was first introduced by Cullen referring to diseases of the nervous system in which there were no obvious physical lesion. It evolved to a wide use with the assumption of an aetiological meaning in the psychodynamic literature. Partially as a result, it has been removed as an organizing principle in psychiatric classifications subsisting, however, in the heading of one group of disorders of ICD-10. Nevertheless, in the clinical context, the terms “neuroticism” and “neurotic” are often used as an informal diagnostic for a relatively large group of patients described as presenting both depressive and anxiety symptoms of fluctuating, chronic pattern and frequently associated with underlying maladaptive personality traits. Most interestingly, a sparking debate subsists among clinicians and researchers on how to categorize such patients. The concept of dysthymia is challenged by several methodological and epistemological issues, along with a raising number of authors sustaining other constructs as better describing the developmental nature of what Schneider called “the aristocracy of suffering”. The authors address these issues revising the available scientific literature, suggesting that, paradoxically, current classifications on the subject do not effectively describe the core aspects of a common and highly resource-consuming set of patients.